KORELASI ANTARA FREKUENSI PENGGORENGAN IKAN TONGKOL DENGAN KADAR ASAM LEMAK BEBAS, KADAR AIR DAN BILANGAN IOD MINYAK GORENG - Dwimaryam Suciati; Zidni Tazkiyah (Politeknik ATI Padang, 2018)
Cooking oil is a principal need for human as a media to process food stuff. Cooking oil can have damage if had repeatly heated, contact with water, air, and metal. The break down of cooking oil happen when frying cause of oxydation, polymerisasion and hydrolysis. Repeatly heated cooking oil will make undesirable compound like free fatty acid and waste suspension in it. The quality of repeatly heated cooking oil measured according to free fatty acid value, water content, and iodine value parameters by using volumetric and gravimetric methods. The sign of cooking oil quality degradation in each repeated fryings are showed by increase of free fatty acid and water content, but decrease of iodine value. After fourth frying of Euthynnus Affnis C., was obtained free fatty acid value 0.131 %, water content 0.172 % and iodine value 56.167. The result showed that after fourth frying of Euthynnus Affnis C., the free fatty acid and iodine value still eligible with SNI, but water content is beyond of SNI limit.